(untitled) (Palíndromo, 2016)
The article is a reflection / presen- tation on artistic procedures (discursive and visual) adopted by the “mesmo pro- ject”. It proposes an information flow that goes to the writing “in the” art to writing “as” art. From the dissertation PLACE PU- BLISHING - artists and magazines - Va- nessa Schultz, the text addresses issues related the intersection between resear- ch in art and artistic processes. We rea- lize that artists / researchers interested in the use of printed space as exhibition space, dedicated attention not only to the narrative structures (the textual con- tent) as well as the visibility modes (pre- sentations) of his writings, be them an academic work, a book, a magazine or any other discursive/artistic space.